2001
DOI: 10.1039/b103304m
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenative coupling of phenanthroline under hydrothermal conditions: crystal structure of a novel layered vanadate complex constructed of 4,8,10-net sheets: [(2,2′-biphen)Co]V3O8.5

Abstract: 2,2'-Biphenanthroline (2,2'-biphen) formed from 1,10-phenanthroline when a new two-dimensional layered vanadium oxide metal coordination complex, [(2,2'-biphen)Co]V3O8.5, which contains novel 4,8,10-net sheets, was hydrothermally synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(59 citation statements)
references
References 15 publications
1
58
0
Order By: Relevance
“…These reactions represent new routes in constructing novel organic-inorganic hybrid materials. Recently, Liu et al [19] reported the dehydrogenative coupling of phen ligands under hydrothermal condition. However, the coupling of 2,2 0 -bipyridine (2,2 0 -bpy) has not been observed to date though there are lots of organic-inorganic hybrid materials reported in which 2,2 0 -bpy coordinate to metal centers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These reactions represent new routes in constructing novel organic-inorganic hybrid materials. Recently, Liu et al [19] reported the dehydrogenative coupling of phen ligands under hydrothermal condition. However, the coupling of 2,2 0 -bipyridine (2,2 0 -bpy) has not been observed to date though there are lots of organic-inorganic hybrid materials reported in which 2,2 0 -bpy coordinate to metal centers.…”
mentioning
confidence: 99%
“…However, few examples involving the in situ reaction of the organic ligand have been reported. More recently, it has been found that in situ reactions, such as ligand oxidative coupling, hydrolysis and substitution, can occur under hydrothermal and/or nonaqueous solvothermal conditions [17][18][19][20][21]. These reactions represent new routes in constructing novel organic-inorganic hybrid materials.…”
mentioning
confidence: 99%
“…, each Zn atom is coordinated by four nitrogen atoms from three 2,2 0 -bpy ligands with a Zn-N distance of 2.16(2)-2.30(3) Å and N-Zn-N angles of 72.2(8)-172.2 (10). It is noteworthy that there are weak hydrogen bonding interactions between oxygen atoms of [Si 2 W 18 O 62 ] 8-polyoxoanions and hydrogen atoms of bpy (O/C interatomic distances between 2.96 and 3.37 Å .…”
Section: Structure Descriptionmentioning
confidence: 99%
“…One approach for the design of organic-inorganic hybrid materials is to introduce some interesting transition metal complexes, which serve as organic-inorganic bridging ligands, into the covalent backbone of inorganic oxides. The influences of transition metal ions as well as their associated organic ligands have been extensively studied in view of their wide potential in a variety of applications [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Great interest has been focused on the design and synthesis of supramolecular vanadium oxides for their applications to catalysis, sorption, molecular electronics, energy storage, optical materials and ceramics [1][2][3][4]. The properties of the vanadium oxides could be tuned by variations in covalency, geometry and oxidation states, and the crystalline architecture.…”
Section: Introductionmentioning
confidence: 99%